Effects of Supplementation of Yeast Malate Fermented Cassava Chip as a Replacement Concentrate on Rumen Fermentation Efficiency and Digestibility of Nutrients in Heifer - Khampa, Sittisak (Asian Health, Science and Technology Reports, 2009)
The object of this study was to determine the influence of supplementation of yeastmalate fermenting cassava chip as a replacement for concentrate on rumen fermentation efficiency and digestibility of nutrients in heifer. Ten, one year old of dairy heifers with initial body weight of 150 ± 10 kg were randomly divided into two groups and received concentrate at 14% CP (T1), and yeastmalate fermented cassava chip (YMFCC) (T2). The cows were offered the treatment concentrate at 1 % BW and ureatreated rice straw was fed ad libitum. Means were compared using Ttest. All animals were kept in individual pens and received free access to water. The results have revealed that replacement of YMFCC on feed intake was nonsignificantly different, while average daily gain (ADG) and digestibility of nutrients were higher (p<0.05) in heifer fed YMFCC (T2) treatments than received concentrate at 14% CP (T1) (254.3 and 219.4 g/d). In addition, the ruminal pH, ammonianitrogen and blood urea nitrogen concentration were significantly different (p<0.05). The concentration of volatile fatty acid was significantly different especially the concentration of propionic acid was slightly higher in heifer receiving T2 than T1 (22.9 and 20.2 mol/100mol). Supplementation of YMFCC (T2) could improve population of bacteria and fungal zoospore, but decreased populations of Holotrich and Entodiniomorph protozoa in rumen (p<0.05). The results indicate that supplementation of yeastmalate fermented cassava chip (YMFCC) as a replacement concentrate at 14 %CP could improve rumen fermentation efficiency and digestibility of nutrients in dairy heifers.